EXPERIMENT STUDY ON CRACK GROWTH RATE OF ADB610 STEEL UNDER DIFFERENT STRESS RATIOS - WEI Long; WANG ShiYue; LIU GuoShou; YANG XiJie (Jixie qiangdu)
The test of the fatigue crack growth rate under five stress ratios（ R = 0. 1,0. 2,0. 3,0. 4 and 0. 5） is completed used the compact tensile specimen. The test data are processed by using incremental polynomial method and the expressions and curves of crack growth rate under different stress ratios are obtained. The effect of stress ratio on crack growth rate and two important parameters in Paris formula are analyzed. Moreover,the fatigue fractures under different stress ratios are analyzed,and discussed the mechanism of effect on crack propagation rate under different stress ratios.